Gender-Based Digital Divide and Discrimination: A Time Use Analysis in Türkiye - ŞAHANOĞULLARI, NAZLI; BİLGİN, DERYA (CRC Press, 2025)
Access to information and communication technologies (ICTs) offers significant advantages globally. The Internet, enabling real-time interaction, is a key part of ICT. Improved access helps reduce inequalities in digital technology access between countries or groups. Examining the digital divide through gender highlights the disadvantages women face in accessing and using ICTs, potentially leading to digital discrimination. This not only contradicts the goal of ending discrimination against women but also hinders their participation in political, economic, and social spheres. In Türkiye, women have lower computer and Internet usage rates compared to men. Teaching digital skills to women could enhance their competitiveness in the labor market. This study investigates the gender-based digital divide and digital discrimination in Turkey through the Time Use Survey conducted by the Turkish Statistical Institute (Turkstat). By analyzing data on ‘computer use and programming’, ‘information acquisition via computer’, ‘communication via computer’, and ‘computer and video games’, the research explores daily time usage patterns to highlight the differences between men and women in accessing and utilizing digital technology, categorized by age groups, income levels, and education levels. Results show that, almost in all computer-related activities analyzed, men spend more time than women. 2026 selection and editorial matter, Muharrem Kılıç and Sezer Bozkuş Kahyaoğlu; individual chapters, the contributors.